2014
DOI: 10.1080/19315864.2014.959216
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Medication Adherence among Community-Based Individuals with Developmental Disabilities and Mental Illness

Abstract: Psychotropic medications are a common treatment for mental illness in people with developmental disabilities. Medication adherence is a critical determinant of the effectiveness of psychotropic drugs, but psychotropic medication adherence research specific to this population remains limited. This retrospective study analyzed Marketscan ® Multi-State Medicaid Database 2003-2007 data. A total of 3,905 eligible community-based Medicaid enrollees aged 18-64 with dual diagnosis of developmental disability and menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Another study of anti-epileptic medication use in adults with developmental disabilities found higher adherence rates among those living in group homes compared with those living in semi-independent settings and those in family homes (Hom et al, 2015). Additionally, in a study of psychotropic medication use among those with developmental disabilities and mental illness, there was a positive association between outpatient visits and adherence, which the authors felt was due to a better support system (Tan et al, 2015). In the general population modifiable factors associated with improved adherence to hypertension management include education, communication, and reducing pill burden (Klootwyk & Sanoski, 2011).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study of anti-epileptic medication use in adults with developmental disabilities found higher adherence rates among those living in group homes compared with those living in semi-independent settings and those in family homes (Hom et al, 2015). Additionally, in a study of psychotropic medication use among those with developmental disabilities and mental illness, there was a positive association between outpatient visits and adherence, which the authors felt was due to a better support system (Tan et al, 2015). In the general population modifiable factors associated with improved adherence to hypertension management include education, communication, and reducing pill burden (Klootwyk & Sanoski, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Many strategies have been evaluated to improve anti-hypertensive medication adherence. Some effective strategies include encouraging patients, caregivers, and healthcare providers to work together to set therapeutic goals, design and implement a treatment plan, and adjust based on patient progress (Tan et al, 2015); consistently incorporating regular follow-up with the health care system (Ho et al, 2009); and simplifying the treatment regimen (e.g., use of fixed-dose combination medicines, use of long-acting drugs, increasing day's supply per fill, etc. ; Weber et al, 2014;Ritchey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, several sources referred to it, while focusing on other parameters and variables. The information extracted from these sources largely clustered on themes of complexity (Branford et al, 1997; Burrow and Rimmer, 1997), risks (Hom et al, 2015; Rasaratnam et al, 2004; Tan et al, 2015; Van Den Bemt et al, 2007) and team makeup (Ellenor and Frisk, 1977; Van Den Bemt et al, 2007; Venables et al, 2015) with repeated emphasis on education and training (Abbott et al, 2014; Bosner and Belfiore, 2001; Buelow and Shore, 2010; Rasaratnam et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…These variances were seen between the records of GPs, consultants and home care services, again highlighting the risks associated with there being several parties to medication management. Although risks associated with disparate documentation (Burrow and Rimmer, 1997) and complexity of processes (Branford et al, 1997; Van Den Bemt et al, 2007) have been noted, the problems of non-adherence were also identified in the literature (Hom et al, 2015; Rasaratnam et al, 2004; Tan et al, 2015). Interestingly, Hom et al (2015) noted that, where there was adequate supervision, non-adherence rates reduced.…”
Section: Resultsmentioning
confidence: 99%
“…They maintained that the focus should be on eradicating stigma, and building a social and psychological atmosphere in which those diagnosed with mental health issues will find meaning and hope in their lives. Tan et al (2015) found that adherent patients have a higher inclination towards outpatient visits and adherence to psychotropic medication because they are provided with a better support system where various outpatient and community services are at their disposal.…”
Section: Client Centred Elements Of Recovery/ Medication Adherence (Smentioning
confidence: 99%